Quality Assurance Transformation in Higher Education Institutions: Linking Accreditation, Digitalization, and Organizational Performance - Sakuroh, Lilis; Marlina, Reni; Krismayanti, Yanti; Adiningsih, Neni Utami (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the transformation of quality assurance in higher education institutions by linking accreditation, digitalization, and organizational performance within an integrated framework. The research adopts a qualitative approach using a literature study design, drawing on recent scholarly sources, policy documents, and empirical studies to explore contemporary trends and challenges in quality assurance systems. Data were collected through systematic identification, selection, and critical analysis of relevant literature, followed by thematic synthesis to generate conceptual insights. The findings reveal that accreditation has evolved into a strategic instrument that drives institutional alignment, accountability, and continuous improvement. Digitalization is identified as a key enabler that enhances efficiency, transparency, and data-driven decision-making in quality assurance processes. Furthermore, the integration of accreditation and digitalization significantly contributes to improved organizational performance, including academic quality, research productivity, governance effectiveness, and stakeholder trust. The study highlights that institutions with well-integrated quality assurance systems demonstrate greater adaptability and competitiveness in dynamic higher education environments. The results emphasize that successful transformation requires not only technological readiness but also strong leadership and a supportive organizational culture. This study contributes to the literature by offering a comprehensive perspective on how quality assurance transformation can be leveraged as a strategic tool for achieving sustainable institutional excellence.